Form of Urban Dance in Bandar Buyut Village Gunung Sugih District Central Lampung Regency - Agus, Zulfa; Daryanti, Fitri; Mariana Devi Lestari, Goesthy Ayu (Jurnal Seni Tari, 2025)
This study aims to describe the form of the Bandaran dance in Bandar Buyut Village. The Urban Dance is a tribute dance for  the Bandar Pak dancers as well as the opening dance  of the cangget night  event and is presented at the begawi cakak pepadun event during the night of cangget. This study uses a qualitative descriptive approach and data collection techniques carried out through observation, interviews and documentation. The results of the research are in the form of data analysis using textual study theory by Sumandiyo Hadi. The form seen in the Kebandaran dance consists of the following elements: danced by four men with the status  of traditional dancers, has a variety of movements with a rectangular and circular floor pattern, accompanied by a tuyun rain type of percussion  using the musical instruments talo lunik, talo balak, raragan talo lunik, bendei and  gung. The clothes used are kawai logs, pieces, punduk and head makeup using tijjang skullcaps and nupai cloth. The settings used are  in the form of a rarang cage, cloud telapah, tajalan and four umbrellas in white, yellow, red and black. The structure of this dance is divided into three parts, namely the beginning, the middle and the end. The duration of this dance is determined by  the bengali committee and  the  place where the Bandaran dance is carried out in the perverted nuwo or the yard  of the prospective perverted house  called the perverted nijjangken.